Correlation of Body Mass Index with Vitamin D and Parathormone (PTH) in Obese and Overweight Children, Study from a Tertiary Care Hospital of Bangladesh - Shyamaly, Kohinoor Jahan; Karim, Muhammad Rezaul; Tithi, Baraka Badruddoza; Akther, Romana; Parvin, Rokhsana; Begum, Suraiya (Medicine Today, 2023)
Introduction with aim and objectives: Childhood obesity and vitamin D deficiency both are emerging health issues. Vitamin D is essential for normal growth and development and frequently found low in obese and overweight children. The aim of this study was to assess serum vitamin D level, calcium, inorganic phosphate, alkaline phosphatase and parathormone (PTH) in obese and overweight children and to see the correlation between BMI, vitamin D and parathormone. Materials and Methods: This study was conducted at Pediatric Endocrinology clinic of department of Paediatrics of Bangabandhu Sheikh Mujib Medical University from the period of November 2016 to October 2018. We assessed 50 obese and overweight children for serum vitamin D, calcium, inorganic phosphate, alkaline phosphatase, and parathormone and we also tried to find out the correlations among the parameters in this cross sectional study. Results: Endocrine society clinical practice guideline was used to define vitamin D status. Result found that all of the obese/overweight children had low vitamin D (82% had deficiency and 18% had insufficiency). There was a statistically significant negative correlation between BMI and serum vitamin D level and positive correlation between BMI and the parathormone level (p value < 0.05). In this study significant negative association was found between vitamin D level and the PTH level p value <0.05. Conclusion: All the studied obese and overweight had vitamin D deficiency or insufficiency. There was negative correlation between BMI and serum vitamin D level and positive correlation between BMI and the parathormone level (PTH). Medicine Today 2023 Vol.35(1): 52-55